Question Number 104191 by mathocean1 last updated on 19/Jul/20 | ||
$${Given}\:\left({E}\right):{x}^{\mathrm{4}} −\mathrm{10}{x}^{\mathrm{2}} +{q}=\mathrm{0} \\ $$ $${U}={x}^{\mathrm{2}} \:{so}\:\left({E}_{\left({U}\right)} \right)={U}^{\mathrm{2}} −\mathrm{40}{U}+{q}=\mathrm{0}\:. \\ $$ $${We}\:{suppose}\:{that}\:{E}_{\left({U}\right)} {has}\:{two}\:{roots} \\ $$ $${such}\:{as}\:{r}_{\mathrm{1}} <{r}_{\mathrm{2}\:} . \\ $$ $${We}\:{give}\:{also}\:{that}\:{r}_{\mathrm{1}} +{r}_{\mathrm{2}} =\mathrm{40}\:{and} \\ $$ $${r}_{\mathrm{1}} ×{r}_{\mathrm{2}} ={q}. \\ $$ $$\left.\mathrm{1}\right){The}\:{equation}\:{E}\:{has}\:{four}\:{positive} \\ $$ $${solution}.\:{Determinate}\:{them}\:{such} \\ $$ $${that}\:{these}\:{solutions}\:{form}\:{an}\: \\ $$ $${arithmetical}\:{progression}. \\ $$ $$ \\ $$ | ||
Answered by 1549442205PVT last updated on 20/Jul/20 | ||
$$\mathrm{Four}\:\mathrm{roots}\:\mathrm{of}\:\mathrm{eqs}.\left(\mathrm{E}\right)\:\mathrm{are}\::\pm\sqrt{\mathrm{r}_{\mathrm{1}} \:}\:,\pm\sqrt{\mathrm{r}_{\mathrm{2}} \:} \\ $$ $$\mathrm{Since}\:\mathrm{they}\:\mathrm{form}\:\mathrm{an}\:\mathrm{arithmetical} \\ $$ $$\mathrm{progression}\:\mathrm{and}\:\mathrm{r}_{\mathrm{1}} <\mathrm{r}_{\mathrm{2}} ,\mathrm{they}\:\mathrm{arrange}\:\mathrm{from}\:\mathrm{least} \\ $$ $$\mathrm{to}\:\mathrm{bigest}\:\mathrm{values}\:\mathrm{as}:−\sqrt{\mathrm{r}_{\mathrm{2}} }\:,−\sqrt{\mathrm{r}_{\mathrm{1}} }\:,\sqrt{\mathrm{r}_{\mathrm{1}} },\sqrt{\mathrm{r}_{\mathrm{2}} } \\ $$ $$\mathrm{By}\:\mathrm{the}\:\mathrm{property}\:\mathrm{of}\:\mathrm{the}\:\mathrm{arithmetical} \\ $$ $$\mathrm{progression}\:\mathrm{we}\:\mathrm{get} \\ $$ $$\sqrt{\mathrm{r}_{\mathrm{2}} }\:−\sqrt{\mathrm{r}_{\mathrm{1}} }=\mathrm{2}\sqrt{\mathrm{r}_{\mathrm{1}} }\:\Leftrightarrow\mathrm{r}_{\mathrm{1}} +\mathrm{r}_{\mathrm{2}} −\mathrm{2}\sqrt{\mathrm{r}_{\mathrm{1}} \mathrm{r}_{\mathrm{2}} }=\mathrm{4r}_{\mathrm{1}} \\ $$ $$\mathrm{From}\:\mathrm{the}\:\mathrm{hypothesis}\:\mathrm{r}_{\mathrm{1}} +\mathrm{r}_{\mathrm{2}} =\mathrm{40}\:\mathrm{we}\:\mathrm{get} \\ $$ $$\mathrm{40}−\mathrm{2}\sqrt{\mathrm{r}_{\mathrm{1}} \mathrm{r}_{\mathrm{2}} }\:=\mathrm{4r}_{\mathrm{1}} \Leftrightarrow\mathrm{20}−\mathrm{2r}_{\mathrm{1}} =\sqrt{\mathrm{r}_{\mathrm{1}} \left(\mathrm{40}−\mathrm{r}_{\mathrm{1}} \right)} \\ $$ $$\Leftrightarrow\mathrm{400}−\mathrm{80r}_{\mathrm{1}} +\mathrm{4r}_{\mathrm{1}} ^{\mathrm{2}} =\mathrm{r}_{\mathrm{1}} \left(\mathrm{40}−\mathrm{r}_{\mathrm{1}} \right) \\ $$ $$\Leftrightarrow\mathrm{5r}_{\mathrm{1}} ^{\mathrm{2}} −\mathrm{120r}_{\mathrm{1}} +\mathrm{400}=\mathrm{0}\Leftrightarrow\mathrm{r}_{\mathrm{1}} ^{\mathrm{2}} −\mathrm{24r}_{\mathrm{1}} +\mathrm{80}=\mathrm{0} \\ $$ $$\Delta'=\mathrm{144}−\mathrm{80}=\mathrm{64}\Rightarrow\sqrt{\Delta\:}=\mathrm{8} \\ $$ $$\Rightarrow\mathrm{r}_{\mathrm{1}} =\mathrm{12}\pm\mathrm{8}\Rightarrow\mathrm{r}_{\mathrm{1}} =\mathrm{4}\left(\mathrm{r}_{\mathrm{1}} =\mathrm{20}\:\mathrm{is}\:\mathrm{rejected}\right) \\ $$ $$\Rightarrow\mathrm{r}_{\mathrm{2}} =\mathrm{36}.\Rightarrow\mathrm{the}\:\mathrm{roots}\:\mathrm{of}\:\:\mathrm{eqs}.\left(\mathrm{E}\right)\:\mathrm{are} \\ $$ $$\boldsymbol{\mathrm{x}}\in\left\{−\mathrm{6};−\mathrm{2};\mathrm{2};\mathrm{6}\right\} \\ $$ | ||